2010
DOI: 10.1007/s10237-010-0247-1
|View full text |Cite
|
Sign up to set email alerts
|

Contact models of repaired articular surfaces: influence of loading conditions and the superficial tangential zone

Abstract: The superficial tangential zone (STZ) plays a significant role in normal articular cartilage's ability to support loads and retain fluids. To date, tissue engineering efforts have not replicated normal STZ function in cartilage repairs. This finite element study examined the STZ's role in normal and repaired articular surfaces under different contact conditions. Contact area and pressure distributions were allowed to change with time, tension-compression nonlinearity modeled collagen behavior in the STZ, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 59 publications
0
8
1
Order By: Relevance
“…Modelling the opposing cartilage layer as a deformable material would give a more accurate representation of the mechanics in the knee. Owen and Wayne (2011) showed that loading with a deformable cartilage layer results in increased contact area and decreased axial deformation and pore pressure compared with a rigid impermeable indenter; thus our results overestimate the axial deformation and pore pressure. However, the same study also demonstrated that radial and axial stresses and strains are similar in models of repair cartilage with a rigid impermeable indenter or with a deformable cartilage layer.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Modelling the opposing cartilage layer as a deformable material would give a more accurate representation of the mechanics in the knee. Owen and Wayne (2011) showed that loading with a deformable cartilage layer results in increased contact area and decreased axial deformation and pore pressure compared with a rigid impermeable indenter; thus our results overestimate the axial deformation and pore pressure. However, the same study also demonstrated that radial and axial stresses and strains are similar in models of repair cartilage with a rigid impermeable indenter or with a deformable cartilage layer.…”
Section: Discussioncontrasting
confidence: 60%
“…However, the same study also demonstrated that radial and axial stresses and strains are similar in models of repair cartilage with a rigid impermeable indenter or with a deformable cartilage layer. Furthermore, Owen and Wayne's (2011) results suggest that the rigid impermeable indenter may allow for reasonable comparisons between models in some instances. For example, the pore pressure is the highest in their 'NORMBOT' and lowest in their 'REP' models, regardless of how the indenter is modelled.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A biomechanical failure of the collagen network in the STZ is postulated in many hypotheses as related to the development of osteoarthritis 14,59,60 Computational models have also been used to demonstrate how a viable superficial zone is critical to achieving long term survival in repairing articular cartilage 61,62 . This study demonstrates that although this layer is less stiff than the remainder of the tissue in compression, it plays a key role in elevating the dynamic material properties of the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…[2,3,11,13]). Many analytical solutions to the problem of contact interaction of articular cartilage surfaces in joints are available.…”
Section: Introductionmentioning
confidence: 99%